2020
DOI: 10.3390/biom10060819
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine TGF-β1 Maintains the Stability of Foxp3+ Regulatory T Cells via IL-12Rβ2 Downregulation

Abstract: Transforming growth factor beta 1 (TGF-β1) is an immunosuppresive cytokine that plays an essential role in immune homeostasis. It is well known that regulatory T (Treg) cells express TGF-β1; however, the role of autocrine TGF-β1 in the development, function, and stability of Treg cells remains poorly understood. We found that Treg cell-derived TGF-β1 was not required for the development of thymic Treg cells in mice, but played a role in the expression of latency-associated peptide and optimal suppression of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…TGF-β is a pleiotropic cytokine, that is an important mediator during the development of Treg and the maintenance of their immunoregulatory state ( 25 ). Besides Treg, TGF-β is expressed by a multitude of cell types and tissues and participates in the mediation of numerous pathways, including development, wound healing, homeostasis, and cancer ( 26 ).…”
Section: Garp Expression Structure and Functionmentioning
confidence: 99%
“…TGF-β is a pleiotropic cytokine, that is an important mediator during the development of Treg and the maintenance of their immunoregulatory state ( 25 ). Besides Treg, TGF-β is expressed by a multitude of cell types and tissues and participates in the mediation of numerous pathways, including development, wound healing, homeostasis, and cancer ( 26 ).…”
Section: Garp Expression Structure and Functionmentioning
confidence: 99%
“…TGF-β1 is essential for the generation and function of nTreg. 47,48 The addition of TGF-β1 enhances the conversion rate of naive CD4 + T cells into Tregs in the periphery.TGF-β1 secreted by Tregs is partially responsible for maintaining immunosuppressive functions. 8,49 Our experiment also found that the expressions of TGF-β1 mRNA and protein in decidua basalis were increased after progesterone administration.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells can secrete TGF‐β1. TGF‐β1 is essential for the generation and function of nTreg 47,48 . The addition of TGF‐β1 enhances the conversion rate of naive CD4 + T cells into Tregs in the periphery.TGF‐β1 secreted by Tregs is partially responsible for maintaining immunosuppressive functions 8,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The downstream molecules such as Smad3 and STAT5 of TGF-β and IL-2 signaling pathways, respectively, play a critical role for Treg generation and Foxp3 stability via binding to conserved non-coding sequences (CNS) in the Foxp3 gene locus ( 35 ). TGF-β signaling also supports Treg stability by prevention of conversion into IFN-γ-expressing cells through inhibition of IL-12R expression ( 36 ). These results indicated that IL-2 and TGF-β are pivotal in Treg homeostasis in preventing autoimmunity.…”
Section: Cytokines and Treg Stabilitymentioning
confidence: 99%